1998
DOI: 10.1103/physrevb.58.7668
|View full text |Cite
|
Sign up to set email alerts
|

Polarized x-ray-absorption spectra ofTiS2,TiSe2,<

Abstract: We studied the anisotropy of the unoccupied electron states of three titanium dichalcogenides by means of polarized x-ray-absorption spectroscopy. The experimental spectra of TiS 2 , TiSe 2 , and TiTe 2 at the Ti K edge and of TiTe 2 at the Te L 1 edge were compared with the results of real-space multiple-scattering calculations. The local angular momentum projections of the densities of states at the titanium sites are presented for energies up to 25 eV above the Fermi level. The Ti K-edge spectra of all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Titanium has a formal 3d 0 confi guration in TiS 2 , which allows for extensive hybridization of empty metal 3d orbitals with unoccupied S 3s * and 3p * antibonding orbitals. Thus, the S K-edge feature of TiS 2 is also split by the crystal fi eld into two peaks of nearly equal intensity (Wu et al 1997, Fleet et al 2005c, and is fairly well reproduced by multiple-scattering calculations (Wu et al 1997, Bocharov et al 1998. The edge features of the S L-edge XANES spectra for niningerite (MgS) and oldhamite (CaS) are strong (Farrell et al 2002), but remain diffi cult to assign in terms of simple L 3 ,L 2 doublets, even after fairly rigorous theoretical study .…”
Section: S L-edge Xanes Spectramentioning
confidence: 81%
“…Titanium has a formal 3d 0 confi guration in TiS 2 , which allows for extensive hybridization of empty metal 3d orbitals with unoccupied S 3s * and 3p * antibonding orbitals. Thus, the S K-edge feature of TiS 2 is also split by the crystal fi eld into two peaks of nearly equal intensity (Wu et al 1997, Fleet et al 2005c, and is fairly well reproduced by multiple-scattering calculations (Wu et al 1997, Bocharov et al 1998. The edge features of the S L-edge XANES spectra for niningerite (MgS) and oldhamite (CaS) are strong (Farrell et al 2002), but remain diffi cult to assign in terms of simple L 3 ,L 2 doublets, even after fairly rigorous theoretical study .…”
Section: S L-edge Xanes Spectramentioning
confidence: 81%
“…The maximum absorption anisotropy for TiS 3 occurs in the (0 0 1) plane of the layer unit, rather than normal to the layer unit as in the MX 2 chalcogenides [17,18,21], wurtzite-type nitrides [20], and V 2 O 5 [19]. This difference in the orientation of the anisotropy is probably related to the presence of two strongly-bonded and mutually perpendicular features in the layer unit of the trisulfide: the TiS 6 chain (the quasi-one-dimensional structural unit) parallel to the b-axis and the disulfide group parallel to the a-axis (Fig.…”
Section: Polarization Effectsmentioning
confidence: 98%
“…X-ray absorption spectroscopy is also sensitive to anisotropy of crystal structure because the absorption edge features are dependent on both the initial and final electron states, thus permitting the anisotropy of conduction states to be probed. Layer-structure compounds, like the transitionmetal chalcogenides, hexagonal nitrides, and V 2 O 5 , have been particularly well studied in this respect [17][18][19][20][21]. The last of these studies investigated the polarized X-ray absorption of the hexagonal CdI 2 -structure chalcogenides TiS 2 , TiSe 2 and TiTe 2 , which have uniaxial physical (optical, electric, magnetic) properties and maximum anisotropy parallel to the c-axis.…”
Section: Introductionmentioning
confidence: 98%
“…Both Ti K-edge and Te L 1 -edge XANES spectra display distinct polarization dependence [19,22]. Similarly to in the case of ZnS, the convergence of the calculated spectra with respect to the size of the cluster is different for the Ti and the Te edges: it was found that at least 51 atoms are needed to get a converged Ti-edge spectrum (a cluster of 25 atoms is insufficient), while 105 atoms are needed to get a converged Te-edge spectrum (57 atoms are far too few) [19].…”
Section: Xanes Spectra Of Titementioning
confidence: 99%